2022
DOI: 10.1038/s41390-022-02040-9
|View full text |Cite
|
Sign up to set email alerts
|

Why monitor the neonatal brain—that is the important question

Abstract: A key goal of neonatal neurocritical care is improved outcomes, and brain monitoring plays an essential role. The recent NEST trial 1 reported no outcome benefits using aEEG monitoring compared to clinical seizure identification among neonates treated for seizures. However, the study failed to prove the effects of monitoring on seizure treatment in the first place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…EEG is a highly complex and detailed signal that requires experienced clinicians, pediatrics, or neonatal EEG specialists to interpret [32,33]. Therefore, the current clinical utility of this technology at the neonatal intensive care units (NICUs) is limited to units with access to experts.…”
Section: Insights On the Utility Of Computer-aided Diagnostic Algorithmsmentioning
confidence: 99%
“…EEG is a highly complex and detailed signal that requires experienced clinicians, pediatrics, or neonatal EEG specialists to interpret [32,33]. Therefore, the current clinical utility of this technology at the neonatal intensive care units (NICUs) is limited to units with access to experts.…”
Section: Insights On the Utility Of Computer-aided Diagnostic Algorithmsmentioning
confidence: 99%
“…[3][4][5] Evidence is also emerging that earlier treatment is associated with better seizure control and reduced overall seizure burden. [6][7][8] However, earlier treatment is possible only if continuous EEG monitoring is available to identify the exact onset of seizures. 6,[9][10][11] Unfortunately, multicenter studies have clearly shown that there can be long gaps between the onset of seizures and the administration of first treatment, and the reasons for this are multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is also emerging that earlier treatment is associated with better seizure control and reduced overall seizure burden 6–8 . However, earlier treatment is possible only if continuous EEG monitoring is available to identify the exact onset of seizures 6,9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG) recording is required, as in human newborns, to both confirm the nature of the paroxysmal events as well as to identify subclinical electrographic seizures. 13 The duration of EEG recording in rodent pups poses a challenge as there are many barriers for continuous or prolonged EEG recording, including frequent nursing by dams and rapid growth of the skull that compromises the placement of the electrodes. But it is crucial to allow appropriate conclusions to be drawn with regard to the antiseizure properties of drugs.…”
mentioning
confidence: 99%
“…This might also limit the exploration of polytherapy in immature rodents due to the inability to provide such vital support/intensive care. Electroencephalography (EEG) recording is required, as in human newborns, to both confirm the nature of the paroxysmal events as well as to identify subclinical electrographic seizures 13 . The duration of EEG recording in rodent pups poses a challenge as there are many barriers for continuous or prolonged EEG recording, including frequent nursing by dams and rapid growth of the skull that compromises the placement of the electrodes.…”
mentioning
confidence: 99%